2019
DOI: 10.1080/10538720.2019.1568337
|View full text |Cite
|
Sign up to set email alerts
|

Does it get better? LGBTQ social work students and experiences with harmful discourse

Abstract: Though the field of social work is grounded in social justice, the social work educational experience, including classrooms, may not live up to this value, especially forLGBTQ students. Using a qualitative phenomenological approach, this study examined the experiences of harmful discourse in social work classrooms for LGBTQ students.Findings indicate that students experienced being misgendered, tokenized, and erased through cis-/hetero-normative language and classroom teachings. Though social work is guided by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Atteberry‐Ash et al. (2019) study of 12 LGBTQ social work students in the United States reported that nine of them described experiences of ‘being excluded, dismissed, or minimized based on other students’ religious identification’ (p.230). By contrast, Barker’s (2013, p.17) study of Christian social work students in the United States reported that they themselves felt excluded by liberal political ideology in social work programmes.…”
Section: Analysis Of Findingsmentioning
confidence: 99%
“…Atteberry‐Ash et al. (2019) study of 12 LGBTQ social work students in the United States reported that nine of them described experiences of ‘being excluded, dismissed, or minimized based on other students’ religious identification’ (p.230). By contrast, Barker’s (2013, p.17) study of Christian social work students in the United States reported that they themselves felt excluded by liberal political ideology in social work programmes.…”
Section: Analysis Of Findingsmentioning
confidence: 99%
“…While Smits et al (2020) analyzed heteronormative speech and casual use of homonegative slurs in young men in sports and found that this language was used almost devoid of meaning except to express lack of masculinity, disapproval, and negativity, concluding that this use of speech attributes to the preservation of heteronormative discourse in spite of growing acceptance of non-heterosexual male athletes. Another study finds that many LGBTQIA+ social work students experience an overwhelming amount of discrimination, mostly perpetuated through harmful discourse (Atteberry-Ash et al, 2019). Lastly, King (2016) finds that heteronormative speech and policing of gender roles in children lead to hypermasculine and violent men, concluding that violence to the queer community can all be connected to heteronormativity in everyday life.…”
Section: Negative Impact Of Heteronormativitymentioning
confidence: 99%
“…While Smits et al (2020) analyzed heteronormative speech and casual use of homonegative slurs in young men in sports and found that this language was used almost devoid of meaning except to express lack of masculinity, disapproval, and negativity, concluding that this use of speech attributes to the preservation of heteronormative discourse in spite of growing acceptance of non-heterosexual male athletes. Another study finds that many LGBTQIA+ social work students experience an overwhelming amount of discrimination, mostly perpetuated through harmful discourse (Atteberry- Ash et al, 2019). Lastly, King (2016) finds that heteronormative speech and policing of gender roles in children lead to hypermasculine and violent men, concluding that violence to the queer community can all be connected to heteronormativity in everyday life.…”
Section: Negative Impact Of Heteronormativitymentioning
confidence: 99%